Targeted delivery of silver nanoparticles and alisertib: in vitro and in vivo synergistic effect against glioblastoma. (June 2014) - Locatelli, Erica; Naddaka, Maria; Uboldi, Chiara; Loudos, George; Fragogeorgi, Eirini; Molinari, Valerio; Pucci, Andrea; Tsotakos, Theodoros; Psimadas, Dimitrios; Ponti, Jessica; Franchini, Mauro Comes
Aim : Targeted biocompatible nanoplatforms presenting multiple therapeutic functions have great potential for the treatment of cancer.Materials & methods : Multifunctional nanocomposites formed by polymeric nanoparticles (PNPs) containing two cytotoxic agents – the drug alisertib and silver nanoparticles – were synthesized. These PNPs have been conjugated with a chlorotoxin, an active targeting 36-amino acid-long peptide that specifically binds to MMP-2, a receptor overexpressed by brain cancer cells.Results : The individual and synergistic activity of these two cytotoxic agents against glioblastoma multiforme was tested both in vitro and in vivo . The induced cytotoxicity in a human glioblastoma–astrocytoma epithelial-like cell line (U87MG) was studied in vitro through a trypan blue exclusion test after 48 and 72 h of exposure. Subsequently, the PNPs' biodistribution in healthy animals and their effect on tumor reduction in tumor-bearing mice were studied using PNPs radiolabeled with 99m Tc.Conclusion : Tumor reduction was achieved in vivo when using silver/alisertib@PNPs–chlorotoxin. Original submitted 8 April 2013; Revised submitted 19 December 2013